Auditory lifestyles, attitudes to noise and beliefs about hearing loss and hearing protection among undergraduates in southern Nigeria (2019)
Noise tolerance is a possible reflection of the attitudes of young people, and probably influenced by beliefs on hearing loss and the use of hearing protection devices. This study addressed the attitudes and beliefs of young Nigerians towards noise thereby providing background data that is necessary for design of culturally relevant interventions to reduce noise exposure and hearing loss. This study determined the attitude towards noise and beliefs about hearing loss and hearing protection among young people in Nigeria. It was a cross-sectional study using semi-structured questionnaires was conducted. The subjects were 427 university undergraduate students. Data was collected on their attitudes to noise and beliefs about hearing protection and hearing loss. Youths Attitude to Noise (YANS) and Beliefs about Hearing Protection and Hearing Loss (BAHPL) instruments were completed by the subjects. Majority of the subjects had neutral attitude towards noise and neutral attitude in Beliefs About Hearing Protection and Hearing Loss while only a minority used any form of hearing protection devices. Indifference is the main attitude of young Nigerians towards noise and hearing loss. Future interventions should focus on the harmful effects of noise, emphasizing the need to avoid exposure to loud noise while encouraging use of hearing protection devices during noise exposure